High-Tolerance Grating Couplers for Vertical Backside Coupling - Chen, Jui-Hung; Bouamra, Arthur D.; Wu, Chia-Ling; Fiore, Andrea; Tseng, Shuo-Yen (Applied sciences, 2024)
To facilitate convenient packaging of photonic integrated circuits on a fiber tip, a silicon grating coupler designed for vertical backside coupling has been developed. In order to comply with foundry capabilities and streamline the fabrication processes, the grating coupler features a minimum feature size larger than 200 nm and a single-etched structure on silicon. By inverse design-based optimization, the vertical backside grating coupler achieves a coupling efficiency of nearly 40% (−3.97 dB), while showcasing high fabrication and misalignment tolerance.